Heroes of our nation : 50 nation builders of Guyana (Guyana. Ministry of Education. Department of Culture, Youth and Sport GeorgetownGY, 2016)
Focuses on men and women who through their work, made, and continue to make significant contributions to changing the environment, thinking and circumstances of the Guyanese people.
Keywords: CULTURAL HERITAGE